PENGARUH PEMASARAN HIJAU TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN MINOMLOK COFFE MEET DAN EATERY - Satriadi, Satriadi; Asep Supriatna; Tubel Agusven; Surya Kusuma (Bajang Institute, 2024)
The purpose of this study was to determine the effect of green marketing on purchasing decisions at Minomlok Coffee Meet and Eatery. This study uses a quantitative research type. Data collection techniques in this study were questionnaires, literature and documentation. Population and employee samples at the Center for Information Technology and Communication The population in this study were visitors to the Minomlok Coffee Meet and Eatery, which was estimated to be 1,000 people per month. The sample for this study were 258 visitors to Minomlok Coffee Meet and Eatery with an error rate of 5%. Data analysis techniques in this study used validity tests, reliability tests, classical assumption tests, simple linear regression analysis tests and hypothesis testing. From the results of the data analysis of the independent variable, namely green marketing, has an effect on the dependent variable, namely purchasing decisions, indicated by the t-count value of green marketing of 11,605 > the t-table value of 1.9692. The magnitude of the influence of green marketing variables is 34,2% on purchasing decisions. While the remaining 65,8% is influenced by other variables. Based on the results of this study, it is concluded that partially green marketing variables have a significant effect on purchasing decisions at Minomlok Coffee Meet and Eatery.